1996
DOI: 10.1103/physrevb.53.14406
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-oscillations in the high-magnetic-field state of(TMTSF)2ClO

Abstract: We report a systematic study of the anomalous rapid oscillation ͑RO͒ phenomena in the quasi-onedimensional organic metal ͑TMTSF͒ 2 ClO 4 in pulsed magnetic fields up to 51 T. We argue that the temperature and magnetic-field dependence of the RO amplitudes in the high-field state result from the reconstructed, nested Fermi surface topology at low temperatures in high magnetic fields. In this topology, the RO amplitudes depend on competing magnetic breakdown and Bragg reflection probabilities, along with Lifshit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The sudden increase of R 0 and of the RO amplitude is consistent with previous results. 8 On the other hand, by deuteration of the ClO 4 salt, T AO increases from 24 K to 27 K, and the transition field to the first and last semimetallic SDW phase increases from 6.5 T to 7 T and from 8 T to 9.7 T, respectively. In addition, the field of the broad peak shifts to the high field side and the phase boundary at high field β HI is not observed below 28 T. This indicates that deuteration of the ClO 4 salt moves the FISDW phase boundary towards the high pressure side and β HI is pushed out above 28 T. These results are regarded as the consequence of a positive chemical pressure in the crystal FIG.…”
Section: Resultsmentioning
confidence: 99%
“…The sudden increase of R 0 and of the RO amplitude is consistent with previous results. 8 On the other hand, by deuteration of the ClO 4 salt, T AO increases from 24 K to 27 K, and the transition field to the first and last semimetallic SDW phase increases from 6.5 T to 7 T and from 8 T to 9.7 T, respectively. In addition, the field of the broad peak shifts to the high field side and the phase boundary at high field β HI is not observed below 28 T. This indicates that deuteration of the ClO 4 salt moves the FISDW phase boundary towards the high pressure side and β HI is pushed out above 28 T. These results are regarded as the consequence of a positive chemical pressure in the crystal FIG.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are several recent explanations for the RO in the FISDW, none of them are satisfactory. Recently, Brooks et al 20 suggested that the combination effects of the reconstructed and nested FS, MB, and BR result in closed orbits which causes the conventional SdH or dHvA effects in the HFS above 28 T and below 5.5 K. The temperature and field dependence in this region is explained by the Lifshitz-Kosevich formula with reasonable parameter. Uji et al also ascribed their RO II to dHvA oscillations in the FS reconstructed by the SDW and the AO.…”
Section: A the Origin Of Two Rapid Oscillationsmentioning
confidence: 94%
“…On the other hand, Brooks et al 20 proposed that the RO in the HFS above 28 T results from the magnetic breakdown ͑MB͒ of the reconstructed, nested FS topology. The temperature and field dependence of the RO is explained with the competation between MB and Bragg reflection ͑BR͒ probabilities, along with Lifshitz-Kosevich reduction factors.…”
Section: Introductionmentioning
confidence: 98%
“…The rapid oscillations have been observed in many experiments. 30,31,47 Although some explanations for the rapid oscillations have been proposed [32][33][34][53][54][55][56][57][58][59][60] for the N = 0 phase, the rapid oscillations in the N = 1 phase have not been understood yet.…”
Section: Introductionmentioning
confidence: 99%